Above the trenches - Hale, Nathan, 1976- (Hale, Nathan, 1976- Nathan Hale's hazardous tales., 2023)
"The first American pilots to fight in World War I flew for the French military. France created a squadron of volunteer Americans called the Lafayette Escadrille (named after the great Marquis de Lafayette). Follow this squadron on their high-flying adventures: How they got into the French military. How they learned to fly. How they fought--and died. And how these American pilots would go down in history with other legendary flying aces, like the Red Baron and his Flying Circus."--